THE MODEL OF PROFESSIONAL COMPETENCE â BASED TEACHING SUPERVISION ON HIGH SCHOOL CHEMISTRY (SPK-SMA-BKP) - Herwanti, Katarina (The Journal of Educational Development, 2014)
The comprehensive subject mastery and learning strategy are competences which must be possessed by chemistry teachers so that they are able to conduct their teaching professionally. As the time goes by, teachers as the main components in learning process are demanded to continuously grow and develop both their knowledge and skills. Teaching supervision is teaching guidance which is conducted by a supervisors to the teachers by providing professional assistance and service so that teachers become more competent in doing their tasks. Teaching guidance, which has precise and exact targets, conducted meticulously, programmed, and continuously, is very useful for the growth and the improvement of teaching quality and of teachersâ career. This study used Research and Development approach. The subjects of this study are 17 Chemistry teachers in Salatiga and 9 supervisors. The aim of this research is to devise the model of teaching supervision for high school chemistry teachers. Several steps were conducted which were 1) describing the model of the current high school chemistry teachers supervision, 2) constructing the model design, 3) validating the model design, 4) piloting the model design, 5) constructing final model ofÂ  professional competence â based teaching supervision on high school chemistry (SPK-SMA-BKP). This teaching supervision model requires a supervisor which is competent in supervising chemistry teaching, masters all high school teaching competencies, understands the basic principles and is experienced in conducting professional development continuously. In order to ensure the fulfillment of supervisionâs aim, the teaching supervision will be conducted three times for each period of supervision so that the profile of chemistry teachersâ performance can be obtained comprehensively. Consequently, the diagnosis of strength and weaknesses can be conducted which leads to teaching supervision suitable for the needs of chemistry teachers.